(untitled) (Quaderni di Gargnano, 2022)
This study presents the idea that the crisis of "pure philosophism" (Gilson) that Dante suffered after the Vita nuova does not occur primarily in the Convivio, as traditional interpretation would have it. Rather, it is expressed in the canzoni written between 1290 and 1300, which Dante would later attempt to correctively reinterpret in the Convivio, and which he finally collected, in his Libro delle Canzoni, as a structured prelude to the Commedia’s narrative. To accept this hypothesis, however, it is necessary on the one hand to read the canzoni as a formal series and, on the other hand, to recognize their allegorical nature. In questo contributo si presenta l’idea che la crisi del "filosofismo puro" (Gilson), sofferta da Dante dopo la Vita nuova, non si verifica tanto nel Convivio, come vuole l’interpretazione tradizionale, quanto nelle canzoni degli anni 1290-1300, che poi Dante avrebbe cercato di reinterpretare in forma correttiva nel Convivio e avrebbe infine raccolto nel Libro delle Canzoni per creare l’antefatto narrativo della Commedia. Per accogliere questa ipotesi, tuttavia, occorre da una parte leggere le canzoni in modo seriale e, dall’altra parte, accorgersi della loro natura allegorica.